USEFULNESS OF MANAGEMENT ACCOUNTING SYSTEMS INFORMATION AND MARKET COMPETITION ON STRATEGIC BUSINESS UNIT OUTPUT - YULIUS KURNIA SUSANTO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2010)
The research examines the interaction effect between the intensity of market competition and the usefulness of broad scope and timeliness management accounting systems (MAS) information characteristics on strategic business unit (SBU) performance and job satisfaction. Fifty six SBU managers from manufacturing industry in Java and Sumatra had participated in the research. The collecting data used a questionnaire survey via electronic-mail and post. Data were analyzed using a moderated regression analysis. The results showed that the higher the intensity of market competition, the more positive the relationship between the usefulness of timeliness MAS information characteristic, SBU performance and job satisfaction. On the contrary the effect of the intensity of market competition on the relationship between the usefulness of broad scope MAS information characteristic, SBU performance and job satisfaction was not significant.